Analisis Pemahaman Wajib Pajak dan Iklan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Dalam Pajak Bumi dan Bangunan di KPP Tangerang Timur - Nico Darmawan (Universitas Multimedia Nusantara, 2012)
This research was conducted to analyze relationship between the understanding of the taxpayer and the tax advertising towards compliance of taxpayer to pay Land and Building Tax (PBB) in the Tax Office (KPP) East Tangerang especially in sub-district Ciledug. Objects of this research are taxpayers who pay PBB in KPP East Tangerang especially in sub-district Ciledug and had seen tax advertising in both mass media and electronic media. The samples were taken by non-probability sampling method by using convenience sampling. The total samples used in analysis are 100 respondents. In the technique of data analysts, this research do the validity test by pearson correlation, reliability testing with coefficient Cronbach’s alpha, the classical assumption test, hypothesis testing multiple regression, t test, and F test. The result showed that the understanding of taxpayer have a significant effect on compliance of taxpayer and the tax advertising have insignificant effect on compliance of taxpayer, meanwhile the understanding of taxpayer and tax advertising simultaneously had a significant effect on compliance of taxpayer. Keywords: Tax Advertising, Compliance of Taypayer, The Understanding of Taxpayer